Evaluasi Kebijakan Pemberdayaan Masyarakat Oleh Badan Usaha Milik Desa (BUMDES) Di Desa Lintong Nihuta Kecamatan Tampahan Kabupaten Toba - Natalia Sihombing; Tunggul Sihombing (Professional: Jurnal Komunikasi dan Administrasi Publik, 2023)
The research method used is descriptive qualitative in order to describe the actual phenomenon of events in the field. Data collection techniques use interviews, observations, and documentation related to the study. The results showed that the implementation of community empowerment that was carried out experienced several obstacles in terms of infrastructure due to limited funds owned and the lack of participating communities because they were still thinking primitively. Therefore, the researcher conducted an evaluation with William N Dunn's evaluation theory which included effectiveness, efficiency, adequacy, leveling, responsiveness and accuracy as benchmarks in this study. Researchers found that the biggest obstacle lies in the source of funds which is still very minimal and then continued by HR problems. The next step is for researchers to provide some inputs such as collaborating with third parties to cover up funding problems, and to provide training to the community in managing business units as a step to cultivate an entrepreneurial spirit.